Social Support, Quality of Life, and Financial Toxicity Among Patients with Hepatocellular Carcinoma - Liu S; Xie Y; Li T; Huang Y; Xu D; Cai L; Fu Y; Chen J; Zhang Y; Huang J; Hu Z (Journal of Hepatocellular Carcinoma)
Shuyue Liu,1– 3,* Yawen Xie,1– 3,* Tiantian Li,1– 3,* Yanxia Huang,1– 3 Danting Xu,1– 3 Linli Cai,1– 3 Yizhen Fu,1– 3 Jinbin Chen,1– 3 Yaojun Zhang,1– 3 Jia Huang,4 Zili Hu1– 3 1Department of Liver Surgery, Sun Yat-Sen University Cancer Center, Guangzhou, 510060, People’s Republic of China; 2Collaborative Innovation Center for Cancer Medicine, State Key Laboratory of Oncology in South China, Sun Yat-Sen University Cancer Center, Guangzhou, 510060, People’s Republic of China; 3Guangdong Provincial Clinical Research Center for Cancer, Sun Yat-Sen University Cancer Center, Guangzhou, 510060, People’s Republic of China; 4Reproductive Medicine Center, The First Affiliated Hospital, Sun Yat-Sen University, Guangzhou, 510060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jia Huang, Reproductive Medicine Center, The First Affiliated Hospital, Sun Yat-sen University, No. 58 Zhongshan Er Road, Guangzhou, Guangdong, 510060, People’s Republic of China, Tel +86 13828442672, Email hjia@mail.sysu.edu.cn Zili Hu, Department of Liver Surgery, Sun Yat-sen University Cancer Center, No. 651 Dongfeng Road East, Guangzhou, Guangdong, 510060, People’s Republic of China, Tel +86-20-87343115, Email huzl1@sysucc.org.cnBackground & Aims: Despite the significant hepatocellular carcinoma (HCC) patient population, gaps exist in understanding their survivorship journey.Methods: Patients diagnosed with HCC at all stages were recruited at Sun Yat-sen University Cancer Center from August 1, 2023, to December 30, 2023. The comprehensive score for financial toxicity (COST) was used to assess financial toxicity, the Functional Assessment of Cancer Therapy-Hepatobiliary (FACT-Hep) was used to assess quality of life (QOL), and the Social Support Rating Scale (SSRS) was used to assess social support. Separate multiple linear regression models were performed to assess the association among social support, FT, and QOL.Results: Of the 250 approached HCC patients, 239 completed the survey and were included in this study. Most respondents were male (192 [80.3%]), of Han nationality (235 [98.3%]), and married (214 [89.5%]). Higher social support (β, 0.13; 95% CI, 0.01 ~ 0.26; P = 0.048) was independently associated with lower FT (higher COST score). Lower FT (β, 0.74; 95% CI, 0.49 ~ 0.99; P < 0.001) and social support (β, 1.47; 95% CI, 0.73 ~ 2.21; P < 0.001) were independently associated with higher QOL. Social support not only directly affected the QOL (b = 0.62, P< 0.001, 95% CI [0.33– 0.90]) but also indirectly affected the QOL through FT (b = 0.14, 95% CI [0.03– 0.28]).Conclusion: The findings of this survey study suggest that social support was associated with higher QOL and lower FT in HCC patients. Future investigations focusing on targeted social support interventions may enhance QOL and reduce FT in HCC patients.Keywords: social support, quality of life, financial toxicity, hepatocellular carcinoma, cross-sectional survey